Workplace communication for graduating students: a quickguide - Md Zamin, Ainul Azmin; Kassim, Rosnani; Abd Majid, Faizah; Kamarudin, Rafidah; Mohamad, Maslawati; Md Zahidi, Azizah (Kulliyah of Islamic Revealed Knowledge and Human Sciences, 2021)
This book is designed to equip students with English communication skills that are required for their future careers. Whether they are active job seekers or aspiring job creators, great communication skills would pave way for success in any career or industry. Effective communication is crucial in the 21st century professional world as good communication helps to build positive working relationship. Workers need to be able to effectively communicate their ideas and listen to co-workers’ ideas. The topics in this book provide the essential communication skills needed before as well as during employment. From writing online resumes that will impress potential employers, to carrying meaningful conversations at work, students are guided through comprehensive, step-by-step explanations. Each explanation is enhanced with elaborations and activities that are practical and easy for students to comprehend. This book is ideal for graduating students and their instructors.